2010
DOI: 10.1002/chem.201000961
|View full text |Cite
|
Sign up to set email alerts
|

High‐Speed Living Polymerization of Polar Vinyl Monomers by Self‐Healing Silylium Catalysts

Abstract: This contribution describes the development and demonstration of the ambient-temperature, high-speed living polymerization of polar vinyl monomers (M) with a low silylium catalyst loading (≤ 0.05 mol % relative to M). The catalyst is generated in situ by protonation of a trialkylsilyl ketene acetal ((R)SKA) initiator (I) with a strong Brønsted acid. The living character of the polymerization system has been demonstrated by several key lines of evidence, including the observed linear growth of the chain length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 72 publications
0
38
0
1
Order By: Relevance
“…[8] From the perspective of this dual activation, the versatility offered by NHCs was attractive. The hydrosilylation would be the first step towards the organocatalyzed one-pot reduction of nonactivated carbon-carbon multiple bonds, whereas the tBuOK-catalyzed reaction is limited to some activated alkynes.…”
mentioning
confidence: 99%
“…[8] From the perspective of this dual activation, the versatility offered by NHCs was attractive. The hydrosilylation would be the first step towards the organocatalyzed one-pot reduction of nonactivated carbon-carbon multiple bonds, whereas the tBuOK-catalyzed reaction is limited to some activated alkynes.…”
mentioning
confidence: 99%
“…[33] In the silyldiazenido complexes 16 and 17,t he NMR resonances of the 29 Si nucleus are shiftedt oh igh field, strongly suggesting that the positive chargei sn ot carried by the Si atom. [34] The actual electronic situation in the group 6c omplexes 14-17 remains debatable and calculations are under way to better appreciate it. This shouldallow detailed comparison with Szymczak's and Ashley's examples.…”
Section: Adducts Between Iron-n 2 Complexes and Strong Lewis Acids Fomentioning
confidence: 99%
“…In addition, acid organocatalysts, such as triphenylmethyl tetrakis(pentafluorophenyl)borane, [18][19][20][21] (R)-3,3'-bis[3,5-bis(trifluoromethyl)phenyl]-1,1'-binaphthyl-2,2'-disulfonimide, 22 trifluoromethanesulfonimide, [23][24][25][26] N-(trimethylsilyl)triflylimide, 27,28 and 1-[bis(trifluoromethanesulfonyl)methyl]-2,3,4,5,6-pentafluorobenzene, 25,26 were suitable for the controlled/living unstable SKA. For the former issue, Taton et al reported that NHC was efficient for the synthesis of block copolymers composed of methacrylate and acrylate monomers, N,N-dimethylacrlamide, and methacrylonitrile.…”
Section: -Tert-butyl-444-tris(dimethylamino)-22-bis[tris(dimethylmentioning
confidence: 99%